Activity-based Management of Logistic Costs in a Manufacturing Company: A Case of Increased Visibility of Logistics Costs in a Slovenian Paper Manufacturing Company - Krajnc, Julijana; Logožar, Klavdij; Korošec, Bojana (Promet - Traffic&Transportation, 2012)
Both the transparent reporting of logistics costs and the related accounting of their cost drivers present a significant factor for the successful management of material flows and the related logistics activities in production companies. These costs, which are mainly reported as part of overhead (indirect) costs in such companies, usually remain hidden or are not explicitly visible when the traditional method of accounting is applied. The aim of this research is to create a model of activity-based accounting of logistics costs in a production company, and to test its efficiency in the disclosure of logistics costs compared with traditional cost accounting. The application of the model in a production company shows that an activity-based approach discloses as much as 108% more logistics costs at the level of a group of products than the traditional cost-accounting approach. Further, detailed information on logistics costs obtained in this way enables their more efficient management. Key words: logistics costs; activity-based costing; cost allocation; cost visibility; cost management